En-block resection of a giant retroperitoneal lipoma presented as huge abdominal swelling: a case report - Bagree, Rajendra; Agrawal, Rishab; Gupta, Sweta; Panwar, Pradeep; Shukla, Veena; Sanjay, R. (International Surgery Journal, 2021)
Retroperitoneal lipomas are an extremely rare entity with only less than 20 cases described in the literature so far. They can attain immoderate size due to space provided in the retroperitoneum and cause abdominal symptoms like abdominal pain, swelling and obstipation due to mass effect. Case presented here as of 53 years old male with complaint of abdominal swelling that had been progressive for the last 1 year. On computed tomography (CT) it revealed giant retroperitoneal mass? liposarcoma? occupying the space immensely. Intraoperatively, two giant retroperitoneal tumours were found which did not show any features of infiltration to nearby structures, therefore the sole tumour annihilation was achieved, which was diagnosed as benign lipoma on histopathology report later. The most important differential diagnosis is the well differentiated liposarcoma, which could only be confirmed after resection and histopathological assessment. Retroperitoneal lipomas are clearly not distinguishable from well differentiated liposarcomas on CT guided and USG guided biopsy and thus it could be misleading. Hence surgical resection with negative margins along with histopathological confirmation is treatment of choice with regular follow up to diagnose early recurrence if any.